Complementary and integrative medicine for breast cancer patients – Evidence based practical recommendations. (August 2016) - Witt, C.M.; Cardoso, M.J.
Abstract: On average half of the breast cancer patients' population uses complementary and integrative medicine (CIM) therapies and many of them would like to receive information on CIM from their conventional treatment team. However, often they don't feel comfortable in discussing CIM related questions, with their conventional treatment team, because they think they don't have enough expertise and available time to deal with this topic. Furthermore, information on the evidence of CIM is not easily accessible and the available information is not always reliable. The purpose of the current paper is to provide: 1) an overview about the CIM interventions that have shown positive effects in breast cancer patients and might be useful in supportive cancer care, 2) practical guidance on how to choose and find a qualified referral to a CIM treatment: 3) recommendations on how these interventions could be integrated into Breast Cancer Centers and which factors should be taken into consideration in this setting. This paper takes available CIM practice guidelines for cancer patients and previous research on CIM implementation models into account. There are CIM interventions that have shown a potential to reduce symptoms of cancer or cancer treatments in breast cancer patients and the vast majority uses a non-pharmacological approach and have a good potential for implementation. Nevertheless, further and more rigorous research is still needed. Highlights: On average half of the breast cancer patients' population uses complementary and integrative medicine (CIM) therapies. Patients often don't feel comfortable in discussing CIM related questions with their conventional treatment team. Some CIM interventions have shown positive effects in breast cancer patients and might be useful in supportive cancer care. It is important, in the conventional setting, to inquire patients about their interest in CIM interventions. It is important, in the conventional setting, to give practical guidance on how to choose and find a qualified referral to a CIM treatment.